Pharmacokinetics of fluoxetine in horses following oral administration. Issue 1 (7th November 2021) - Waitt Wolker, Laura H.; Veltri, Charles A.; Pearman, Krista; Lozoya, Maria; Norris, Jeffrey W.
Abstract: This study aimed to investigate pharmacokinetics of fluoxetine in horses and validate a method for liquid chromatography mass spectrometry analysis of serum levels. Fluoxetine pharmacokinetics were determined using 10 healthy, adult horses. Fluoxetine pharmacokinetics following a single oral dose (0.25 mg/kg) were determined using blood samples collected prior to and at several time points over 7 days following administration. Serum concentrations of fluoxetine and its bioactive metabolite norfluoxetine were measured using liquid chromatography coupled to an accurate mass/high‐resolution mass spectrometer. Pharmacokinetic parameters were estimated using a noncompartmental model. Time to maximum serum concentration and serum half‐life of fluoxetine was 1.5 and 15.6 h, respectively. Steady‐state serum concentrations were evaluated using five horses each receiving fluoxetine (0.25 mg/kg, PO, q24hrs) for 8 weeks and were found to be 62.9 ± 25.5 ng/ml on average. Norfluoxetine was not detected in any sample.